Acupuncture methods for allergic rhinitis: a systematic review and bayesian meta-analysis of randomized controlled trials - Zihan Yin; Guoyan Geng; Guixing Xu; Ling Zhao; Fanrong Liang (BMC, 2020)
Abstract Background Allergic rhinitis (AR) is a common symptomatic, inflammatory, and immunological disorder of nasal mucosa. Multiple clinical trials and systematic reviews have implicated acupuncture methods as potentially effective treatment strategies for AR, however, considering the great burden of AR, it is crucial to explore the most recent clinical evidence supporting acupuncture in AR. Besides, the methodologies reported in previous studies as well as those commonly applied during clinical practices greatly vary. Herein, we conducted network meta-analysis to compare the effectiveness of diverse acupuncture methods for AR treatment. Methods We conducted a literature search for relevant reports published from inception to 1 July 2020 in several scientific databases, including PubMed, Embase, Cochrane library, Web of Science, CNKI, WF, VIP, CBM, AMED as well as related registration platforms. Primary outcomes as reported in the identified studies were assessed using nasal symptoms. All Meta-analyses were performed with RevMan, ADDIS, and STATA software. To ensure consistency among our reviewers, the intra-class correlation coefficient was used. Results Exactly 39 studies with 3433 participants were covered in this meta-analysis. The meta-analysis demonstrated that all acupuncture types were superior to sham acupuncture in terms of total nasal symptom score and rhinoconjunctivitis quality of life questionnaire. Moxibustion was recommended as the most effective intervention as it reduced nasal symptoms in 6 treatments. On the other hand, manual acupuncture plus conventional medicine was recommended as the most effective intervention in improving the quality of life in 9 treatments. Notably, moxibustion was recommended as the most effective intervention that changed the content of IgE in 9 treatments. Moreover, adverse events of these interventions were acceptable. Conclusion Our findings revealed that all acupuncture methods are effective and safe for AR. Moreover, either moxibustion or manual acupuncture plus conventional medicine are potentially the most effective treatment strategies for AR. Based on these findings, it is evident that acupuncture therapy is not inferior to pharmacologic therapy. Therefore, for AR patients who are either unresponsive to conventional medicine or are intolerant to adverse events, acupuncture therapy should be administered. However, the quality of these included trials was mainly ranked as moderate quality, we recommend additional well-designed RCTs with larger sample sizes to validate these findings.